Designing a prototype trauma registry framework for a tertiary health institution in a low- and middle-income country: A qualitative study. - Helen Adesoba; Adesola Olumide; Kehinde Oluwadiya; Ajibola Oladiran; Kehinde Ojifinni; Oluwafemi Popoola; Carl Bonander (PLoS ONE)
Introduction Low- and middle-income countries experience high injury-related mortality rates, with road traffic crashes being a significant contributor in Nigeria. Data from trauma registries are crucial for designing and advocating for trauma intervention programmes. However, there is limited research to inform the development of trauma registries in a Nigerian setting. The aim of this study was to design a feasible prototype trauma registry (TR) including, scope of activities and registry components for University College Hospital (UCH), Ibadan, Nigeria. Methods In-depth interviews were conducted with eight purposively selected trauma registry stakeholders in UCH to obtain context-specific information for a prototype registry. An expert meeting was conducted with four purposively selected experts within the hospital to assess and validate the suitability of the prototype TR scope and TR components, confirming their applicability and potential efficacy in UCH. Information obtained from the interviews and expert meeting were analysed deductively using thematic analysis. Results Stakeholders identified the most feasible scope for the trauma registry (TR) as daily data collection on all trauma patients from their initial presentation to discharge or death. This data would be gathered primarily at two critical points: the accident/emergency department and the wards where trauma patients are admitted. Stakeholders believed that comprehensive information about trauma patients could be achieved through these collection points. Following this scope, the analysis led to the identification of 21 essential components and activities for the TR, which were then organised into six categories: registry personnel, computers and other materials, trainings, technology infrastructure, administrative services, and monitoring and evaluation. Conclusion The scope and components identified are relevant to our context and have the potential to contribute to trauma prevention programmes, improve patient care and outcomes, and contribute to trauma-related policies and programmes if successfully implemented.